Long-term trajectories of BMI and cumulative incident metabolic syndrome: A cohort study - Ying, Ming; Hu, Xiangming; Li, Qiang; Dong, Haojian; Zhou, Yingling; Chen, Zhujun (Frontiers in Endocrinology, 2022)
Background: Body mass index (BMI) has been widely recognized as a risk factor for metabolic syndrome (MetS). However, the relationship between the trajectory of BMI and incident MetS is still unclear. We investigate the associations of long-term measurements of BMI with MetS among young adults in the China Health and Nutrition Survey. Methods: We enrolled individuals aged 10 to 20 at baseline with recorded BMI at each follow-up interview, and 554 participants were finally included in our study. The assessment and incidence of MetS were evaluated by blood tests and physical examinations in their adulthood. A latent class growth mixed model was used to identify three BMI trajectory patterns: a low baseline BMI with slow development (low-slow, n=438), a low baseline BMI with fast development (low-fast, n=66), and a high baseline BMI with fast development (high-fast, n=50). Logistic regression was used to explore the relationship between different BMI trajectories and the incidence of MetS. Result: During a follow-up of 16 years, 61 (11.01%) participants developed MetS. The combination of elevated triglycerides and reduced high-density lipoprotein cholesterol was most frequent in diagnosed MetS. In multivariate adjusted models, the low-fast and high-fast BMI trajectories showed a significantly higher risk of MetS than those with the low-slow BMI trajectory (low-high: OR = 3.40, 95% CI: 1.14-10.13, P < 0.05; high-fast: OR = 5.81, 95% CI: 1.63-20.69, P < 0.05). Conclusion: Our study identified three BMI trajectories in young adults and found that long-term measurements of BMI were also associated with incident MetS.